Dualism and Unworthy Legal Practice: The Marginalization of Women's Rights in Sirri and Early Marriages - Hasan, Abi; Musyahid, Achmad; Asman, Asman (UIN Sunan Kalijaga, 2022)
Abstract: Marriage is a constitutional right of Indonesian citizens, but not all marriages end in favour to women. From a legal and normative standpoint, this study examines how sirri and early marriage marginalize women. This article is library research. Datas were collected by conducting study of primary and secondary legal materials. The findings of this study demonstrate that sirri marriage is manifestly ineffective and contrary to the Indonesian Marriage Law. Women in sirri marriages do not have proper inheritance rights because sirri marriages are not recognized by state law, despite the fact that they are valid under religious law. In a similar vein, it appears that women's rights are not guaranteed in early marriage because couples in general lack the capacity and maturity to manage rights, obligations, and roles within the household; even early marriage appears to be